2019
DOI: 10.1186/s12868-019-0493-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of hemodynamic change during 8 MHz transcranial focused ultrasound stimulation using near-infrared spectroscopy

Abstract: BackgroundTranscranial focused ultrasound (tFUS) attracts wide attention in neuroscience as an effective noninvasive approach to modulate brain circuits. In spite of this, the effects of tFUS on the brain is still unclear, and further investigation is needed. The present study proposes to use near-infrared spectroscopy (NIRS) to observe cerebral hemodynamic change caused by tFUS in a noninvasive manner.ResultsThe results show a transient increase of oxyhemoglobin and decrease of deoxyhemoglobin concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…DCS-diffuse correlation spectroscopy) and tissue oxygenation (static NIRS) (Hosomi et al, 2019;Hou et al, 2019). It is an attractive and accessible approach to investigate brain activity changes with its high temporal resolution, robustness to electrical artefacts, and low cost (Kim et al, 2019). The device measures relative changes in oxygenated-(oxy-), deoxygenated-(deoxy-) and total Hb concentrations, and oxygen saturation using different wavelengths (Hosomi et al, 2019;Hou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DCS-diffuse correlation spectroscopy) and tissue oxygenation (static NIRS) (Hosomi et al, 2019;Hou et al, 2019). It is an attractive and accessible approach to investigate brain activity changes with its high temporal resolution, robustness to electrical artefacts, and low cost (Kim et al, 2019). The device measures relative changes in oxygenated-(oxy-), deoxygenated-(deoxy-) and total Hb concentrations, and oxygen saturation using different wavelengths (Hosomi et al, 2019;Hou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…6. COMSOL 3-DIMENSIONAL ANALYSIS Studies using higher frequencies of 27.38 M H z and 8 M H z by [37] and [126] used intensities of I SP P A 0.465 W /cm 2 and I SP P A 12 and 5.2 W /cm 2 , respectively. Studies, using lower frequencies in general used higher intensities or pressures such as 1.76 M P a at 2 M H z by [29], I SP P A 34.96 W /cm 2 at 2.32 M H z by [127], I SP P A 46 W /cm 2 at 2 M H z by [128] and I SP P A of 8.93 W /cm 2 and pressure of 0.51 M P a at 2.9 M H z by [129].…”
Section: Comparison Between Simulation and Literaturementioning
confidence: 99%
“…Two studies examined the neuromodulation effect on the S1 with wide-field optical imaging (Choi et al, 2019) and near infrared spectroscopy (NIRS) measurements (Kim et al, 2019a). Both of the studies showed that neuronal calcium signaling was at least twice that observed in peripheral regions.…”
Section: Neuromodulatory Effect Of Tus In Animalsmentioning
confidence: 99%